Does Local Wisdom Improve Quality of Public Services?: Learn from the Bugis-makassar Culture - Hasniati; Hamdat, Supriadi; Fatimah, Siti; Haslinda Zainal, Nining (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to explore local wisdom which can be the basis for improving the quality of public services through cultural values, customs and traditions and messages of ancestors from the Bugis-Makassar Society. The long-term goal of this research is to make local wisdom values the basis for developing the principles of public service quality. The intention is to preserve the local wisdom of Bugis-Makassar, which is becoming extinct before being identified. Research data sources are Lontara’s Pappaseng manuscript, history books, and articles. This study used a qualitative analysis as the interpretation of the historical, sociological, religious and cultural phenomenon in public services. The results of this study are the discovery of several local wisdom that has developed in the Bugis-Makassar community, namely:acca,lempu’, getteng, and siri’napacce’sculture. If these values are internalized and practiced in the form of behavior, it will improve the quality of public services.